Uporaba sup210 Pb za datiranje in sledenje procesom v okolju - Urbančič, Matej (Matrika, 2023)
210Pb is a radioactive isotope with a half life of 22,2 years. It is present in air, Earth’s crust as well as in living oragnisms. It can be used for following erosion processes and dating sediment layers on shore or on seabed that are up to 200 years old. 210Pb can also be used to estimete degree of antropogenic lead pollution in water, plants and soil. Another possible application of 210Pb is to find out the share of lead present in a plant that comes from air and the share that comes from soil.
Keywords: dating; datiranje; jedrska fizika; lead; nuclear physics; radioactive decay; radioaktivni razpadi; svinec